Lanabecestat: Neuroimaging results in early symptomatic Alzheimer's disease - Zimmer, Jennifer A.; Shcherbinin, Sergey; Devous, Michael D.; Bragg, Sonja M.; Selzler, Katherine J.; Wessels, Alette M.; Shering, Craig; Mullen, Jamie; Landry, John; Andersen, Scott W.; Downing, AnnCatherine M.; Fleisher, Adam S.; et al. (Alzheimer's & dementia : translational research & clinical interventions, 2021)
Introduction Lanabecestat, a beta‐site amyloid precursor protein‐cleaving enzyme 1 (BACE1) inhibitor, was investigated as a potential Alzheimer's disease (AD)‐modifying treatment. As previously reported, amyloid beta (Aβ) neuritic plaque burden reduction did not result in clinical benefit. Lanabecestat's effects on neuroimaging biomarkers and correlations between neuroimaging biomarkers and efficacy measures are reported. Methods AMARANTH and DAYBREAK‐ALZ were 104‐ and 78‐week, multicenter, randomized, double‐blind, placebo‐controlled studies of lanabecestat in early symptomatic AD (AMARANTH) and mild AD dementia (DAYBREAK‐ALZ). Patients randomly (1:1:1) received placebo, lanabecestat 20 mg, or lanabecestat 50 mg daily (AMARANTH, n = 2218; DAYBREAK‐ALZ, n = 1722). Florbetapir positron emission tomography (PET), fluorodeoxyglucose (FDG) PET, flortaucipir PET, and volumetric magnetic resonance imaging (MRI) were used to measure Aβ neuritic plaque burden, cerebral metabolism, aggregated tau neurofibrillary tangles, and brain volume, respectively. Additionally, florbetapir perfusion scans were performed in DAYBREAK‐ALZ. Efficacy measures included 13‐item Alzheimer's Disease Assessment Scale–Cognitive Subscale, Alzheimer's Disease Cooperative Study Activities of Daily Living Inventory, Clinical Dementia Rating–Sum of Boxes, Functional Activities Questionnaire, and Mini‐Mental State Examination. These studies stopped early due to futility. Results Despite previously observed annualized reduction in Aβ neuritic plaque burden, there were no treatment differences in annualized change of aggregated tau neurofibrillary tangle burden (AMARANTH, n = 284; DAYBREAK‐ALZ, n = 70), cerebral metabolism (AMARANTH, n = 260; DAYBREAK‐ALZ, n = 38) and perfusion (DAYBREAK‐ALZ, n = 213). Greater brain volume reduction (AMARANTH, n = 1697 [whole brain]; DAYBREAK‐ALZ, n = 650 [whole brain]) occurred on lanabecestat compared to placebo. Higher baseline aggregated tau neurofibrillary tangle burden, lower cerebral metabolism, and lower brain volumes correlated with poorer baseline efficacy scores and greater clinical worsening. Lower baseline cerebral perfusion correlated with poorer baseline efficacy scores. Reduction in cerebral metabolism or whole brain volume correlated with clinical worsening, regardless of treatment assignment. Discussion Tau pathology and cerebral metabolism assessments showed no evidence of lanabecestat slowing pathophysiologic progression of AD. Lanabecestat exposure was associated with brain volume reductions. Correlations between imaging measures and cognitive assessments may aid future study design.